2005
DOI: 10.1167/iovs.05-0368
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Association of Endothelial Nitric Oxide Synthase Gene in Subjects with Glaucoma and a History of Migraine

Abstract: This study provides evidence of an association between the NOS3 gene and subjects with glaucoma who have a history of migraine. Unlike in other studies, no evidence was found of an association between ET-1 and glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
4
33
1
2
Order By: Relevance
“…In the overall analysis, we observed a marginal difference in the frequency of this polymorphism among cases and controls, which was not significant after adjustments for other variables of interest. These results are in accordance with the findings observed by other authors (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). The Glu298Asp polymorphism, in turn, has been associated with risk of ischemic shock (Berger et al, 2007), coronary spasm (Yoshimura et al, 1998), coronary artery disease (Colombo et al, 2003;Hingorani et al, 1999), myocardial infarction (Hibi et al, 1998;Shimasaki et al, 1998) and NAION (Sakai et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the overall analysis, we observed a marginal difference in the frequency of this polymorphism among cases and controls, which was not significant after adjustments for other variables of interest. These results are in accordance with the findings observed by other authors (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). The Glu298Asp polymorphism, in turn, has been associated with risk of ischemic shock (Berger et al, 2007), coronary spasm (Yoshimura et al, 1998), coronary artery disease (Colombo et al, 2003;Hingorani et al, 1999), myocardial infarction (Hibi et al, 1998;Shimasaki et al, 1998) and NAION (Sakai et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…While some studies have implicated polymorphisms in the promoter region or inside the eNOS in the risk of POAG (Ayub et al, 2010;Liao et al, 2011;Tunny et al, 1998), other authors found no significant association (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). Interestingly, recent reports indicate that these different polymorphisms could interact with other exposure factors in modulating the risk of POAG, such as gender, use of postmenopausal hormones (PMHs), hypertension and smoking (Kang et al, 2010(Kang et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively more consistent associations are observed with genetic studies of eNOS-related factors and POAG. [62][63][64][65][66][67] Although not all studies have found associations with variants in the NOS3 gene that codes for eNOS, 68,69 variants or haplotypes of SNPs in NOS3 have been reported to be associated with POAG overall, 62,65 POAG with migraines, 66 POAG or high tension POAG among women only, 63,64 and familial POAG. 67 Furthermore, the CAV1/CAV2 gene region, which codes for caveolins that control eNOS activity, contain variants associated with POAG in one GWAS, 24 and this finding was replicated in another large candidate gene study.…”
Section: Discussionmentioning
confidence: 99%
“…The 27-bp VNTR has been associated with variations in plasma levels of nitric oxide and its metabolites [16,17]. The association between eNOS mRNA levels and the 4-repaet allele appeared to be dosedependent [18].…”
Section: Discussionmentioning
confidence: 94%